2009
DOI: 10.1007/s00380-008-1115-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum myeloperoxidase level predicts reperfusion in patients with myocardial infarction receiving thrombolytic therapy

Abstract: Polymorphonuclear leukocytes play a central role in all stages of the atherothrombotic inflammatory process. The atherothrombotic activity of polymorphonuclear leukocytes is exerted by mediators such as myeloperoxidase (MPO). Although the role of MPO has been studied with respect to the development of adverse cardiac events in acute coronary syndromes (ACS), the association of this molecule with effectiveness of reperfusion in patients receiving thrombolysis is not yet known. The study population consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In our study, we used serum collection tubes as they had been used in a previous large observational study enrolling patients with acute coronary syndromes where MPO levels were found to predict the clinical outcome. 4 Similar studies have also reported an association between serum MPO levels and myocardial reperfusion after thrombolysis 5 and systemic inflammation after a primary percutaneous coronary intervention, 6 thus indicating that MPO measured in serum is clinically meaningful. Finally, the findings in our clinical study are consistent with those in our postmortem tissues from sudden coronary deaths that showed a higher density of MPO-positive cells in thrombi overlying eroded lesions relative to plaque rupture.…”
mentioning
confidence: 76%
“…In our study, we used serum collection tubes as they had been used in a previous large observational study enrolling patients with acute coronary syndromes where MPO levels were found to predict the clinical outcome. 4 Similar studies have also reported an association between serum MPO levels and myocardial reperfusion after thrombolysis 5 and systemic inflammation after a primary percutaneous coronary intervention, 6 thus indicating that MPO measured in serum is clinically meaningful. Finally, the findings in our clinical study are consistent with those in our postmortem tissues from sudden coronary deaths that showed a higher density of MPO-positive cells in thrombi overlying eroded lesions relative to plaque rupture.…”
mentioning
confidence: 76%
“…In these patients, baseline MPO was an independent predictor of in-hospital mortality (OR 3.9, 95% CI, 1.8-7.5). Only one study (42) exa mined the association of the serum MPO level and the response to thrombolytic treatment in 158 patients with ST-segment MI. MPO levels before thrombolysis were significantly lower in patients with successful reperfusion.…”
Section: Myeloperoxidase and Acute Coronary Syndromementioning
confidence: 98%